PENGUATAN MANAJEMEN PROYEK KEGIATAN SOSIAL DAN KEMASYARAKATAN DI KOMUNITAS - Ahmad Jet Alamin A; Parlaban Karo-Karo; Raliman Febby P. Purba S (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This Community Service Program (PKM) activity aims to strengthen project management for the implementation of social and community activities in partner communities. Common problems encountered include unstructured activity planning, unclear task allocation, poor volunteer management and communication, unmapped activity risks (permits, weather, security, logistics), and substandard post-activity reporting and evaluation. The program is implemented through needs assessments, core project management training, workshops on developing work tools (project charter, WBS, timeline, RACI, budget, risk management, SOP), activity execution simulations, and implementation assistance for one community project. The output is a ready-to-use project management toolkit that can be replicated for subsequent community activities.